Toolbox of Effects of CO2 Impurities on CO2 Transport and Storage Systems. (July 2017) - Neele, Filip; Koornneef, Joris; Jakobsen, Jana Poplsteinova; Brunsvold, Amy; Eickhoff, Charles
Abstract: There is a need to gather new knowledge on the fundamental properties of CO2 mixtures with impurities and their impact on the chain integrity and economics of Carbon Capture & Storage (CCS) chains. One of the main results from the FP7 IMPACTS project is the IMPACTS toolbox, which comprises new experimental data, thermodynamic reference models for CO2 mixtures relevant for CCS and the framework for CCS risk assessment taking Health Safety & Environment aspects, the impact of the quality of the CO2 and CCS chain integrity into account, and finally the recommendations report.